2012
DOI: 10.1242/jcs.111310
|View full text |Cite
|
Sign up to set email alerts
|

Class E compartments form in response to ESCRT dysfunction in yeast due to hyperactivity of the Vps21 Rab GTPase

Abstract: SummaryThe endosomal sorting complexes required for transport (ESCRTs) mediate the budding of intralumenal vesicles (ILVs) at late endosomes. ESCRT dysfunction causes drastic changes in endosome morphology, which are manifested in Saccharomyces cerevisiae by the formation of aberrant endosomes known as class E compartments. Except for the absence of ILVs, the mechanistic basis for class E compartment biogenesis is unknown. We used electron microscopy to examine endosomal morphology in response to transient ESC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 70 publications
10
73
0
Order By: Relevance
“…On the basis of our data, we consider it likely that CORVET drives the stacking of endosomes, although it should be kept in mind that only the Vps8 subunit localizes to the class E compartment and is sufficient to cluster multivesicular bodies (14). Interestingly, Russell et al 53 did not observe an multivesicular body sorting defect in the vps21⌬ mutant, even though we (this study) and others (50) did observe this. We consider it likely that these divergent observations are due to the weaker phenotype of the mutant.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…On the basis of our data, we consider it likely that CORVET drives the stacking of endosomes, although it should be kept in mind that only the Vps8 subunit localizes to the class E compartment and is sufficient to cluster multivesicular bodies (14). Interestingly, Russell et al 53 did not observe an multivesicular body sorting defect in the vps21⌬ mutant, even though we (this study) and others (50) did observe this. We consider it likely that these divergent observations are due to the weaker phenotype of the mutant.…”
Section: Discussionsupporting
confidence: 49%
“…It has been shown recently that hyperactive Rab5 homolog Vps21 can trigger the formation of stacked endosomal compartments that mimic the absence of ESCRT proteins (53). On the basis of our data, we consider it likely that CORVET drives the stacking of endosomes, although it should be kept in mind that only the Vps8 subunit localizes to the class E compartment and is sufficient to cluster multivesicular bodies (14).…”
Section: Discussionsupporting
confidence: 48%
“…It is expected that both ESCRT and retromer should have finished their sorting events before an endosome can fuse with the lysosome. Indeed, mature endosomes are filled with vesicles and lack retromer cargo (Russell and Odorizzi , 2012 ), which was sorted into tubular carriers beforehand (Cullen , 2008 ). Interestingly, retromer also binds Rab7, which is the receptor for the HOPS fusion complex and requires this Rab for its recruitment to the endosomal membrane (Rojas et al , 2008 ;Seaman et al , 2009 ).…”
Section: Even Though the Exact Organization Of Such Zonesmentioning
confidence: 99%
“…In addition to these traditional roles, it has recently been demonstrated that Rab5 has a role in maturation of the early to the late endosome [19][20][21] . Deletion of the yeast Rab5 gene, VPS21, results in accumulation of the vacuolar protein Vph1p delivered from the VPS pathway and the cell surface receptor, Ste3p, delivered from the endocytic pathway in distinct vesicles 11 , suggesting that Vps21p can function at two distinct transport steps-vacuolar transport from the TGN and the early-to-late endosome transition, before convergence of the endocytic and VPS pathways.…”
mentioning
confidence: 99%